Gene-by-temperature interactions and candidate plasticity genes for morphological traits in Drosophila melanogaster. - Valeria Paula Carreira (Public Library of Science (PLoS), 2013)
Understanding the genetic architecture of any quantitative trait requires identifying the genes involved in its expression in different environmental conditions. This goal can be achieved by mutagenesis screens in genetically tractable model organisms such as Drosophila melanogaster. Temperature during ontogenesis is an important environmental factor affecting development and phenotypic variation in holometabolous insects. In spite of the importance of phenotypic plasticity and genotype by environment interaction (GEI) for fitness related traits, its genetic basis has remained elusive. In this context, we analyzed five different adult morphological traits (face width, head width, thorax length, wing size and wing shape) in 42 co-isogenic single P-element insertional lines of Drosophila melanogaster raised at 17°C and 25°C. Our analyses showed that all lines differed from the control for at least one trait in males or females at either temperature. However, no line showed those differences for all traits in both sexes and temperatures simultaneously. In this sense, the most pleiotropic candidate genes were CG34460, Lsd-2 and Spn. Our analyses also revealed extensive genetic variation for all the characters mostly indicated by strong GEIs. Further, our results indicate that GEIs were predominantly explained by changes in ranking order in all cases suggesting that a moderate number of genes are involved in the expression of each character at both temperatures. Most lines displayed a plastic response for at least one trait in either sex. In this regard, P-element insertions affecting plasticity of a large number of traits were associated to the candidate genes Btk29A, CG43340, Drak and jim. Further studies will help to elucidate the relevance of these genes on the morphogenesis of different body structures in natural populations of D. melanogaster.